Optimal investiment decisions for two positioned firms competing in a duopoly market with hidden competitors - Armada, Manuel José da Rocha (2011)
This paper extends the literature dealing with the option to invest in a duopoly market for a leader-follower setting. A restrictive assumption embodied in the models in the current literature is that investment opportunities are semi-proprietary in that the two identified or positioned firms are guaranteed to hold at least the follower’s position. More competition is realistically captured in our model by introducing the concept of hidden rivals so that the places in the market can be taken not only by positioned firm but also by these hidden competitors. The value functions and the optimal triggers for the positioned firms differ materially in settings with(out) the presence of hidden rivals. Unlike existing models, our model allows for (a)symmetric market shares and investment costs for the leader and the follower. Cooperative entrance by the two positioned firms is also modeled.